2021
DOI: 10.1088/1755-1315/765/1/012029
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Iron and Manganese from Palm Oil Mill Effluent (POME) using Activated Clinoptilolite Zeolite

Abstract: The adsorption capacity of activated clinoptilolite zeolite for the removal of heavy metal ions; iron Fe(III) and manganese Mn(II) from palm oil mill effluent (POME) was investigated in this batch sorption study. The physicochemical properties of both raw clinoptilolite zeolite and POME effluent were first characterized before the modification of the zeolite is made, chemically and physically. The raw filtered POME has an initial pH of 4.56 which was acidic, whereas the natural zeolite has a slightly alkaline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Briefly, it can be observed that removal patterns for all the adsorbents increased as the pH of the water sample was increased, until the optimum pH was 8. This was due to the deprotonation of oxygen functional groups, which increased the active sites for heavy metal ions chelation and significantly increased the AC adsorption capacity [63]. The results also show that the different metal ions in the solution have different competitive adsorption effects [37].…”
Section: Effect Of Phmentioning
confidence: 87%
“…Briefly, it can be observed that removal patterns for all the adsorbents increased as the pH of the water sample was increased, until the optimum pH was 8. This was due to the deprotonation of oxygen functional groups, which increased the active sites for heavy metal ions chelation and significantly increased the AC adsorption capacity [63]. The results also show that the different metal ions in the solution have different competitive adsorption effects [37].…”
Section: Effect Of Phmentioning
confidence: 87%
“…Furthermore, the repulsion between free metal ions in POME and adsorbed ions reduced additional heavy metal adsorption (Taha et al 2016). Other factors that affect the elimination of contaminants from POME are such as contact time (Aziz et al 2021), agitation speed (AlMoharbi et al 2019, and initial pH (Abbar et al 2017;Khamis and Jalil 2021). Similar to Ng et al (2019), the presence of high levels of organic compounds and suspended solids in the POME resulted in increased turbidity and an unpleasant dark colour solution.…”
Section: Aas Analysismentioning
confidence: 99%